Evaluation of the orthopaedics and traumatology resident education in Turkey: A descriptive study - Gazi Huri; Yusuf Sertan Cabuk; Safa Gursoy; Mustafa Akkaya; Secil Ozkan; Volkan Oztuna; Onder Aydingoz; Alparslan Senkoylu (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objective: The objective of this study is to describe the current situation regarding the training, working conditions, future plans, fields of interest and satisfaction of orthopaedics and traumatology residents in Turkey. Methods: A descriptive survey questionnaire consisting of 24 questions was designed to identify the problems and solution suggestions concerning training of orthopaedic residents. All orthopaedics and traumatology residents who took the 2013 Progress Testing for Speciality in Medicine (UEGS) held by Turkish Orthopaedics and Traumatology Education Council (TOTEK) were surveyed in the class at the end thereof as well as the young orthopaedic surgeons who were reached through the email groups of Turkish Society of Orthopaedics and Traumatology – Residents and Young Attendings Council (TOTBID-AGUH). Results: A total of 725 residents and 132 young attendings were surveyed. The most outstanding answers are as follows: 62,7% of the respondents replied to the question “Is there a training program/Is it being applied” as “yes/yes”. It was found out that 94,3% of the respondents wanted to be involved in a rotation abroad. The “patient care” was the most common answer, with a ratio of 36,9%, to the question “What's the priority of the department you are studying in?”. Regarding work conditions, “many emergency on-calls” was found to be the most important parameter affecting life conditions (p < 0.05). Conclusion: Aiming to identify the challenges that orthopaedics and traumatology residents in Turkey face as regards their training, this survey stands as a pioneering study with a high participation rate. Analysis of survey data highlights the importance of several key factors such as the development of training programs and increasing the time spent with academicians as well as spreading and promotion of log book application. Keywords: Orthopaedics, Residents' training, Resident, Survey, Feedback